Jamaica. Significant achievements 2011 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Jamaica during 2011 are identified, with respect to the needs and interests of the country, strengthening issues such as greenhouses, marketing, research, sustainability, beekeeping, rural development, agrotourism, agricultural development, production, policies public, postharvest, cooperation between the public and private sector, operational techniques, disease control, such as American foulbrood and the ruminant, cassava and herb value chains.